Faith and Power Latino Religious Politics Since 1945. - Hinojosa, Felipe (New York University Press, 2022)
Illuminates how religion shapes Latino politics and community buildingToo often religious politics are considered peripheral to social movements, not central to them. Faith and Power: Latino Religious Politics Since 1945 seeks to correct this misinterpretation, focusing on the post-World War II era. It shows that the religious politics of this period were central to secular community-building and resistance efforts. The volume traces the interplay between Latino religions and a variety of pivotal movements, from the farm worker movement to the sanctuary movement, offering breadth and nuance to this history. This illuminates how broader currents involving immigration, refugee policies, de-industrialization, the rise of the religious left and right, and the Chicana/o, immigrant, and Puerto Rican civil rights movements helped to give rise to political engagement among Latino religious actors. By addressing both the influence of these larger trends on religious movements and how the religious movements in turn helped to shape larger political currents, the volume offers a compelling look at the twentieth-century struggle for justice.